Immune and senescence profiles associated with non-AIDS-defining cancer risk in people with HIV: a case-cohort study - Pita-Martínez, Carlos; Jiménez-Sousa, María Ángeles; Martinez-Picado, Javier; Rodríguez, Carmen Elena Gómez; Fariñas, Carmen; Galindo, Pepa; Roca-Oporto, Cristina; Santos, Jesús; Muñoz-García, Paula; Rava, Marta; Resino, Salvador; Martín-Escolano, Rubén (Frontiers in Immunology, 2025)
IntroductionPeople with HIV (PWH) on effective antiretroviral therapy (ART) have an increased risk of developing Non-AIDS Defining Cancers (NADCs) compared to the general population, partly due to chronic inflammation and immune dysregulation. This study aimed to identify plasma biomarkers associated with the risk of developing NADCs in a cohort of PWH on ART.MethodsA case-cohort study was conducted within the Spanish CoRIS cohort, including 316 PWH on ART (71 cases and 245-individuals subcohort). Plasma levels of 24 immune regulation and senescence-associated secretory phenotype (SASP) biomarkers were quantified using Luminex technology. Cox proportional hazards regression models with Borgan II weights were used to assess the association between biomarker levels and the risk of NADC development (hazard ratios), adjusting for confounders. Effect modification by gender was also evaluated.ResultsHigher baseline plasma levels of twelve biomarkers were significantly associated with increased NADC risk. The strongest associations were found for PD–L2 (aHR=3.33), PAI–1 (aHR=2.27), and MMP–1 (aHR=2.32). However, a distinct, gender-specific pattern was observed, with significant interactions found for nine biomarkers. Most interactions indicated a higher NADC risk increase in females, with the exception of CD80, TNF–β and IP–10, which indicated a relatively lower risk in females compared to males.DiscussionPlasma biomarkers of immune regulation and SASP are associated with NADC risk in PWH on long-term ART, highlighting the importance of gender-specific pathways in NADC development among PWH. Understanding these distinct profiles may guide future strategies for risk stratification, early detection, and personalized preventive care.